Gases Released During Soil Biodisinfestation of Pepper Greenhouses Reduce Survival of Phytophthora capsici Oospores in Northern Spain - Larregla, Santiago; Gandariasbeitia, Maite; Ojinaga, Mikel; Mendarte, Sorkunde; Guerrero, María del Mar; Ortiz-Barredo, Amaia (Frontiers in Sustainable Food Systems, 2021)
Phytophthora root and crown rot of pepper (Capsicum annum L.) is a soilborne plant disease that causes important economic losses worldwide. Phytophthora capsici is one of the species that affects protected pepper crops in different agroclimatic areas of Spain. Currently, environmentally friendly strategies such as biodisinfestation for plant disease control have become increasingly popular. The main objective was to establish the effect solely attributable to released gases during biodisinfestation with fresh animal manure amendments on P. capsici oospore viability. The biodisinfestation trial was performed in a greenhouse located in northern Spain (Biscay), with a mixture of fresh sheep and dry poultry manures (2+0.5 kg.m-2) and soil sealing with transparent polyethylene plastic film 0.05 mm thick for 21 days (onset June-15th). Oospores were incubated at the innocuous controlled temperature of 20ºC and inside vacutainer tubes that were previously placed under vacuum and refilled with gases that were sampled from the aerial cavity of biodisinfested plots at different time intervals throughout the biodisinfestation period. The treatments were different combinations of sampling time intervals (0-1-2-3-4-7-9-11-14 days, succession of days 1-2-3-4-7-9-11-14) and exposure times (7-14-21 days). Three control treatments were included: air-tubes, vacuum-tubes and 15 cm depth biodisinfested soil. Oospore viability was determined with the plasmolysis method. The most effective treatment was the succession of gases collected during all sampling days. The significant but slight reduction in oospore viability by exposure to the different gas treatments was consistent with the low dose of applied amendment and the low soil temperature registered at 15 cm depth during soil biodisinfestation (>25°C–100% time, >35°C–23%, >40°C-3%). The above circumstances might have generated a small quantity of gases with low impact on oospore viability. The biodisinfested soil at 15 cm depth control treatment showed the lowest oospore viability in all the exposure times assayed. The overlap of thermal and higher biofumigation effects in this treatment could likely be responsible for its greater efficacy. A disinfectant effect purely attributable to released gases throughout biodisinfestation has been demonstrated. We believe that our research will serve as a base for future application in agro-environments with reduced thermal inactivation effects.